Empires of the sand the struggle for mastery in the Middle East, 1789-1923 - Karsh, Efraim; Karsh, Inari (Harvard University Press, 2001)
Rejecting the view of modern Middle Eastern history as an offshoot of global power politics, the authors argue that the main impetus for the developments of the momentous long 19th century (1789-1923) came from local actors. They see a pattern of pragmatic cooperation and conflict between the Middle East and the West during the past two centuries.